Kinetics of colour and texture changes of beef during storage - Olivera, Daniela Flavia (2013)
The influence of the packaging films, aerobic and vacuum conditions, and refrigeration storage temperature (0, 4 and 10 °C) on colour and texture of raw meat were studied during a 2-week storage period in order to analyze kinetics of colour and texture changes. The rate of redness decrease was most noticeable at the highest storage temperature and aerobic conditions and these changes were well described by the first-order reaction. Texture parameter reflected a progressive softening during storage for both films. Decrease on shear force of raw beef during storage followed a first-order kinetic model. Temperature dependence of colour and texture change was adequately modelled with the Arrhenius equation.